From Food Waste to Efficient Bifunctional Nonprecious Electrocatalyst. Issue 61 (26th September 2017) - Hof, Ferdinand; Boni, Alessandro; Valenti, Giovanni; Huang, Kai; Paolucci, Francesco; Pénicaud, Alain
Abstract: Synergy between graphitic nanocarbon, obtainable from food waste through cracking of biomethane, and iron oxide nanoparticles provides access to efficient bifunctional electro catalysts. Dissolution of potassium‐intercalated graphitic nanocarbons yields graphenide solutions with calibrated, small lateral size‐reduced graphenes that are used subsequently as reducing agents of iron metal salts. This results in the strong binding of small size (2–5 nm) nanoparticles on the carbon framework homogeneously within the composite material, accessibility of the catalytic centers, and good conductivity provided by the underlying carbon framework. The iron oxide nanocarbon electrocatalyst performances are highlighted by the overall overpotential of approximately 1 V needed to reach the benchmark threshold of 10 mA cm −2 for the oxygen reduction reaction and the particular activity towards oxygen evolution reaction ( η ≈0.4 V at 10 mA cm −2 ), comparable to that of the precious RuO2 and IrO2 catalysts. This iron oxide/nanocarbon electrocatalyst is versatile, remarkably active, stable, and truly sustainable. Abstract : Turning waste into resource : An efficient and bifunctional electrocatalyst for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER), utilizing only earth‐abundant elements and renewable precursors is obtained by reductive dissolution of a sustainable nanocarbon followed by redox chemistry.